Comparing the efficacy of AR-based training with video-based training. (September 2022) - Dwivedi, Shivangi; Hayes, John; Pedron, Isabella; Kang, John; Brenner, Lindsey J.; Barnes, Connor; Bailly, Ashley; Tanous, Kyle; Nelson, Cassidy; Moats, Jason; Gabbard, JosephL.; Mehta, Ranjana K.
In recent years, US Emergency Medical Services (EMS) have faced a massive shortage of EMS workers. The sudden outbreak of the pandemic has further exacerbated this issue by limiting in-person training. Additionally, current training modalities for first responders are costly and time-consuming, further limiting training opportunities. To overcome these challenges, this paper compares the efficacy of augmented reality (AR), an emerging training modality, and video-based training to address many of these issues without compromising the quality of the training with reduced instructor interaction. We examined performance, subjective, and physiological data to better understand workload, user engagement, and cognitive load distribution of 51 participants during training. The statistical analysis of physiological data and subjective responses indicate that performance during AR and video-based training and retention phases depended on gender perception of workload and cognitive load (intrinsic, germane, extraneous). However, user engagement was higher in AR-based training for both genders during training.